2014
DOI: 10.1111/jce.12580
|View full text |Cite
|
Sign up to set email alerts
|

Rate‐Control Drugs Affect Variability and Irregularity Measures of RR Intervals in Patients with Permanent Atrial Fibrillation

Abstract: Modification of AV node conduction by rate-control drugs increase RR variability, while only β-blockers affect irregularity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…They demonstrated that though there were significant differences at baseline between the two groups in respect of HRV (SDRR, RMSDD, LF and HF), these parameters changed in patients with AF in a similar direction albeit visually different magnitudes to healthy individuals when subjected to pharmacological sequential autonomic blockade. In a subsequent blinded crossover trial in 60 patients with permanent AF, it was shown that both beta‐blockers and rate limiting calcium channel blockers lower heart rate and time domain parameters (SDRR, RMSDD), whilst beta‐blockers also increased irregularity (sample entropy; Corino et al., ). Nagayoshi and colleagues documented RR interval and SDRR in 23 patients (mean age 61 years) in response to tilt, Valsalva, hand grip and showed that the response in patients with AF was similar to those of a historic SR population (Nagayoshi, Janota, Hnatkova, Camm, & Malik, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They demonstrated that though there were significant differences at baseline between the two groups in respect of HRV (SDRR, RMSDD, LF and HF), these parameters changed in patients with AF in a similar direction albeit visually different magnitudes to healthy individuals when subjected to pharmacological sequential autonomic blockade. In a subsequent blinded crossover trial in 60 patients with permanent AF, it was shown that both beta‐blockers and rate limiting calcium channel blockers lower heart rate and time domain parameters (SDRR, RMSDD), whilst beta‐blockers also increased irregularity (sample entropy; Corino et al., ). Nagayoshi and colleagues documented RR interval and SDRR in 23 patients (mean age 61 years) in response to tilt, Valsalva, hand grip and showed that the response in patients with AF was similar to those of a historic SR population (Nagayoshi, Janota, Hnatkova, Camm, & Malik, ).…”
Section: Discussionmentioning
confidence: 99%
“…Yamada and colleagues showed in 107 patients with AF and predominately a preserved left ventricular ejection fraction, that HRV (nonlinear markers only) could predict mortality (Yamada et al., ). In the reduced ejection fraction population of MADIT‐II, in a subgroup of patients with AF ( n = 68), those with a pNN20 < 87 had a higher mortality (Corino et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Corino i wsp. ocenili wpływ bursztynianu metoprololu w tabletkach o przedłużonym uwalnianiu, karwedylolu, diltiazemu oraz werapamilu na zmienną i niemiarową odpowiedź komór u 60 pacjentów z utrwalonym migotaniem przedsionków, włączonych do badania skrzyżowanego z następującymi po sobie trzema tygodniowymi etapami leczenia [32]. Przeanalizowano po pięć 20-minutowych segmentów EKG od każdego pacjenta na początku badania oraz podczas ostatniego dnia każdego z etapów badania.…”
Section: Badania Porównawcze Skutecznościunclassified
“…In this issue of the Journal , Corino et al . evaluated 4 common rate‐control drugs by seeking differences on heart rate variability and irregularity in patients with permanent AF previously enrolled in the RATAF study.…”
Section: How Do Drugs Exert Rate Modulation?mentioning
confidence: 99%